What's a Robot? - Cerf, Vinton G. (Communications of the ACM, 2013)
The article presents the author's comments on the history of the robot as a functional machine. Topics include the four laws of robotics created by the science fiction writer Isaac Asimov; the relationship between software development and robots which manipulate physical objects and have a tangible effect; and the social aspects of robotics compared to the computer software industry.